Pre-Service Chemistry Teachers Practicum Experiences in Libya: Challenges, Support Needs, and Supervisors Perspectives - Rania Alrwesse; Abtisam Aljarmi; Najah Baroud (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
Teaching practicum is an important stage in chemistry teacher education because pre-service teachers need to apply what they have learned at the university in real classrooms while facing real constraints such as time, classroom control, safety issues, and limited school resources. This study explores practicum experiences of final-year pre-service chemistry teachers in Libya, focusing on the main challenges they face and the support they need across different school contexts. A convergent mixed-methods design was used, combining a questionnaire with semi-structured interviews to compare students’ and supervisors’ views. Questionnaire data were collected from 60 final-year female pre-service chemistry teachers from the Chemistry Department, Faculty of Education, University of Zawia, who were placed in 9 practicum schools (urban: n = 42; non-urban: n = 18). At the same time, nine practicum supervisors were interviewed to identify recurring difficulties and potential improvements in the practicum program. The survey showed high pressure related to classroom management and limited lesson time, difficulty in teaching abstract chemistry concepts and linking macroscopic, symbolic, and particle-level explanations, and frequent student misconceptions with lower confidence in assessing understanding. Students also reported limited lab access and school resources, and not enough satisfaction with university supervision feedback. The supervisors’ interviews supported these results, pointing to clear time-loss points during lessons, crowded classes that make safety harder, and a common move to demonstration or theory-based lessons when resources are limited. Overall, the findings suggest the need for a stronger support system in practicum, including clearer mentoring, regular observation and feedback, chemistry-focused teaching resources, simple diagnostic assessment tools, and low-cost, safe lab alternatives. This study provides evidence from Libya and gives practical suggestions to improve chemistry teacher preparation and school–university cooperation.